Ethnic Inequality and the Dismantling of Democracy: A Global Analysis. (18th May 2015) - Houle, Christian
Abstract : Does inequality between ethnic groups destabilize democracies? While the literature largely agrees that inequality harms democracies, previous studies typically focus on the overall level of inequality in a society, leaving unanswered questions about the effect of inequality between ethnic groups. This article fills this gap and argues that inequality between ethnic groups harms the consolidation of democracy but that its effect is strongest when inequality within groups is low. Using group- and country-level data from more than seventy-one democracies and 241 ethnic groups worldwide, the author conducts the first cross-national test to date of the effect of ethnic inequality on transitions away from democracy. Results provide support for the hypothesis: when within-ethnic-group inequality (WGI) is low, between-ethnic-group inequality (BGI) harms democracy, but when WGI is high, BGI has no discernable effect.